2006
DOI: 10.1002/gcc.20358
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of familial breast cancer segregates with constitutional t(11;22)(q23;q11)

Abstract: In a family with a high incidence of postmenopausal breast cancer and a case of glioblastoma, the constitutional translocation t(11;22)(q23;q11.2) was shown to segregate with the malignancies. The breakpoints in this family coincided with the common breakpoints in t(11;22) as shown by a translocation-specific PCR assay. Loss of heterozygosity analysis of breast tumor tissue revealed deletion of the normal chromosome 22, but retention of der(22) in the tumor cells, suggesting a predisposing effect of the der(22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Although carriers of the balanced t(11;22)(q23;q11) are generally phenotypically normal, we note that there are reports of increased cancer incidence in these carriers (Lindblom et al 1994;Jobanputra et al 2005;Wieland et al 2006;Carter et al 2010), and speculate that the altered gene expression we observe may underlie this. Furthermore, our observations raise the possibility that translocations in cancer cells may contribute to oncogenesis not only by disrupting the gene, or genes mapping around the breakpoints, but also through changes in expression of genes positioned elsewhere on the affected chromosomes and on other displaced chromosomes, a hypothesis that warrants detailed investigation in the future.…”
Section: Differentially Expressed Genes Show Position Changes Within mentioning
confidence: 44%
See 1 more Smart Citation
“…Although carriers of the balanced t(11;22)(q23;q11) are generally phenotypically normal, we note that there are reports of increased cancer incidence in these carriers (Lindblom et al 1994;Jobanputra et al 2005;Wieland et al 2006;Carter et al 2010), and speculate that the altered gene expression we observe may underlie this. Furthermore, our observations raise the possibility that translocations in cancer cells may contribute to oncogenesis not only by disrupting the gene, or genes mapping around the breakpoints, but also through changes in expression of genes positioned elsewhere on the affected chromosomes and on other displaced chromosomes, a hypothesis that warrants detailed investigation in the future.…”
Section: Differentially Expressed Genes Show Position Changes Within mentioning
confidence: 44%
“…comm.). Carriers of the translocation are phenotypically normal, although some studies have shown they have up to a 10-fold greater risk of developing breast cancer than cytogenetically normal individuals (Lindblom et al 1994;Jobanputra et al 2005;Wieland et al 2006;Carter et al 2010). Carriers are also at risk of having progeny with Emanuel syndrome (OMIM no.…”
mentioning
confidence: 99%
“…Carriers of constitutive balanced translocation between the long arm of chromosome 11 and 22 t (11q:22q) are reported to exhibit increased risk of breast cancer (Lindblom et al, 1994;Wieland et al, 2006). Carriers of constitutive balanced translocation between the long arm of chromosome 11 and 22 t (11q:22q) are reported to exhibit increased risk of breast cancer (Lindblom et al, 1994;Wieland et al, 2006).…”
Section: A the Types Of Chromosomal Translocationsmentioning
confidence: 99%
“…The t(11;22)(q23.3;q11.2) is the most common recurrent reciprocal translocation in humans [Zackai and Emanuel, 1980]. Carriers of this translocation are phenotypically normal, so are usually ascertained following investigation for multiple miscarriages, infertility, or after the birth of a child with supernumerary derivative 22 syndrome (also known as Emanuel syndrome), which results from 3:1 malsegregation of the parental derivative 22 [Fraccaro et al, 1980; Zackai and Emanuel, 1980; Carter et al, 2009]. A small number of reports have suggested an association between the 11;22 translocation and an increased risk of breast cancer in carrier women.…”
Section: To the Editormentioning
confidence: 99%